Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pupuk Organik Cair (POC) dari Sampah Dapur di Dusun Watu, Kalurahan Argomulyo, Sedayu, Bantul - Afifah Azzahra; Hasna Zuhdiyyah Mumtazah; Rofifah Zulfa Azizah; Mohammad Brian Adrian; Sri Puji Ganefati (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
ABSTRACT The problem of organic waste management is one of the main concerns in the working area of the Sedayu I Community Health Center, especially in Watu Hamlet, Argomulyo Village. Although the community understands the importance of waste management, its implementation remains low. The objective of this community service activity is to improve the community's knowledge and skills in managing organic waste through training in the production of Liquid Organic Fertilizer (POC). The methods used include outreach, self-assessment surveys (SMD), training for community leaders, and dissemination to the community. Evaluation was conducted through pre-tests and post-tests. The average pre-test score was 70.6, and the average post-test score was 86.6. The average percentage increase in knowledge among community leaders was 26%. The results of the analysis using the Wilcoxon test showed a significant increase in knowledge among training participants, as the sig value was <0.05. This activity demonstrated that educational methods and hands-on practice can enhance community awareness and capacity in organic waste management.